RF study and 3-D simulations of a side-coupling thermionic RF-gun - S. Rimjaem (2018)
A thermionic RF-gun for generating ultra-short electron bunches was optimized, developed and used as a source at a linac-based THz radiation research laboratory of the Plasma and Beam Physics Research Facility, Chiang Mai University, Thailand. The RF-gun is a π/2-mode standing wave structure, which consists of two S-band accelerating cells and a side-coup ling cavity. The 2856 MHz RF wave is supplied from an S-band klystron to the gun through the waveguide input-port at the cylindrical wall of the second cell. A fraction of the RF power is coupled from the second cell to the first one via a side-coupling cavity. Both the waveguide input-port and the side-coupling cavity lead to an asymmetric geometry of the gun. RF properties and electromagnetic field distributions inside the RF-gun were studied and numerically simulated by using computer codes SUPERFISH 7.19 and CST Microwave Studio 2012 © . RF characterizations and tunings of the RF-gun were performed to ensure the reliability of the gun operation. The results from 3D simulations and measurements are compared and discussed in this paper. The influence of asymmetric field distributions inside the RF-gun on the electron beam properties was investigated via 3D beam dynamics simulations. A change in the coupling-plane of the side-coupling cavity is suggested to improve the gun performance. © 2013 Elsevier B.V. All rights reserved.